The Effectiveness of Chitosan to Increase Body Resistance of Sangkuriang Catfish (Clarias gariepinus) Against Aeromonas hydrophila Attack - Mahatma Kresnha Radityo; Rosidah; Walim Lili; Roffi Grandiosa Herman (Jurnal Akuakultur Indonesia, 2022)
This research aims to determine the optimal dose of chitosan that is appropriate to be given to commercial feed in increasing the immune system of sangkuriang catfish fry. The research was carried out in April – June 2021 at the Aquaculture Laboratory and Biotechnology Laboratory, Faculty of Fisheries and Marine Sciences, Padjadjaran University. This research used an experimental method of Completely Randomized Design (CRD) with five treatments and three replications. The treatment used was the addition of chitosan to feed with doses of 0 g (A), 2.5 g (B), 5 g (C), 7.5 g (D), and 10 g (E). Maintenance of test fish for 14 days. Experimental fish were infected by Aeromonas hydrophila bacteria with a density of 108 CFU/ml with 10 ml immersion method. Parameters observed included white blood cells, leukocyte differential, clinical symptoms, survival and water quality. Data on white blood cell count, and survival were analyzed by ANOVA, if there was a significant difference, Duncan's test was performed. Leukocyte differential data, clinical symptoms and water quality were analyzed descriptively. The results showed that the addition of chitosan at a dose of 10 g was effective for improving the immune system performance of catfish fry. During 14 days of chitosan administration, the white blood cell count increased by 41.60% from the value of 13.96 × 104 cells/mm3 to 23.90 × 104 cells/mm3. The 10 g chitosan treatment was an effective dose to stimulate differential leukocytes in catfish to improve the immune system, it was also marked by the fastest clinical symptom recovery period and the highest survival rate after the challenge test, which was 96.6%.